The recent evolution of consumption poverty in Rwanda - Andy McKay (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This paper analyses the evolution of consumption poverty in Rwanda between 2001/1 and 2010/11, using three comparable good quality household surveys analysed along with detailed price data. Rwanda achieved impressive growth over this period. The first half of the 2000s was associated with slow poverty reduction and an increase in inequality, while in the second half of the period there was faster consumption growth, a sharp fall in poverty, and a modest reduction in inequality. Overall the poverty situation in Rwanda remains sensitive to agricultural conditions when the surveys are conducted.
Keywords: I32; O12; 330; Rwanda; poverty; household surveys; prices